Competing endogenous RNA network analysis reveals pivotal ceRNAs in bladder urothelial carcinoma - Li, Yangle (Transl Androl Urol, 2021)
BACKGROUND: Bladder urothelial cancer (BUC) has become one of the most frequently occurring malignant tumors worldwide and it is of great importance to explore the molecular pathogenesis of bladder cancer. Emerging evidence has demonstrated that dysregulation of noncoding RNAs is critically involved in the tumorigenesis and progression of BUC. Long noncoding RNAs (lncRNAs) can act as microRNA (miRNA) sponges to regulate protein-coding gene expression and therefore form a competing endogenous RNA (ceRNA) network. ceRNA networks have been proven to play vital roles during tumorigenesis and progression. Elements involved in the ceRNA network have also been identified as potential therapeutic targets and prognostic biomarkers in various tumors. Understanding the regulatory mechanisms and functional roles of the ceRNA system will help understand tumorigenesis, progression mechanisms of BUC and develop therapeutics against cancer. METHODS: In this study, we utilized the TCGA database and analyzed the multilevel expression profile of BUC. ceRNA regulatory networks were constructed by integrating tumor progression and prognosis information. RNA immunoprecipitation (RIP) and qRT-PCR were applied to verify the identified ceRNA networks. KEGG enrichment analysis was implemented to infer the biological functions of the regulatory system. RESULTS: We identified a lncRNA–miRNA–mRNA regulatory ceRNA network containing two lncRNAs, one miRNA and 14 mRNAs. The ceRNA network we identified showed significant roles in BUC tumorigenesis, progression, and metastases. CONCLUSIONS: The proposed ceRNA network may help explain the regulatory mechanism by which lncRNAs function as ceRNAs and improve our understanding of the pathogenesis of BUC. Moreover, the candidate elements involved in the ceRNA network can be further evaluated as potential therapeutic targets and prognostic biomarkers for BUC.